Model based analysis of the methane seeping influence on the acidification in the East Siberian Arctic Shelf waters - Yakushev, Evgeniy; Berezina, Anfisa; Shakhova, Natalia; Bruggeman, Jorn; Wallhead, Philip; Staalstrøm, André; Novikov, Matvey; Yakubov, Shamil; Zagovenkova, Anastasia; Ardelan, Murat V.; Bellerby, Richard; Gustafsson, Örjan; et al. (Frontiers in Marine Science, 2025)
A giant Arctic subsea permafrost reservoir of methane (CH4) in different forms (hydrates, free gas) is leaking, likely at an increasing rate under climate warming. This is causing a massive CH4 release from sediments into the water column and atmosphere. A part of the released CH4 is oxidized in the water column to CO2. In this work we applied a model for analyzing of consequences for the water column carbonate system of excessive production of CO2 during the aerobic oxidation of CH4 in an area of its intensive seeping in the East Siberian Arctic Shelf (ESAS). The model system comprised a 2-Dimensional vertical Benthic Pelagic transport Model 2DBP, principal biogeochemistry and carbonate system modules from the biogeochemical model BROM (Bottom RedOx Model), and a gas bubble fate module that parameterizes bubbles rising and dissolution. The simulations showed that consumption of oxygen and production of carbon dioxide via aerobic oxidation of methane results in spatial anomalies of pH and dissolved oxygen concentration that are consistent with the field observations. We hypothesize that aerobic oxidation of methane in the regions of intensive seeping leads to production of CO2, with associated decrease of pH and lowering of aragonite saturation to less than 1, therefore contributing to the extreme acidification states that are observed on the East Siberian Arctic Shelf.